'Quality of Care' Standards in Inflammatory Bowel Disease: A Systematic Review. (13th November 2018) - Fiorino, Gionata; Allocca, Mariangela; Chaparro, Maria; Coenen, Sofie; Fidalgo, Catarina; Younge, Lisa; Gisbert, Javier P
Abstract: Background: Inflammatory bowel disease [IBD] includes chronic, disabling and progressive conditions that need a complex approach and management. Although several attempts have been made to standardize the care of IBD patients, no clear definitions of a global 'standard of care' are currently available. Methods: We performed a systematic review of the available literature, searching for all relevant data concerning three main domains of standards of quality of care in IBD patients: structure, process and outcomes. From the literature search, 2394 abstracts were retrieved, and 62 relevant papers were included in the final review. Results: Standards of quality of care in IBD include several aspects that can be summarized in three identified domains: structure, process and outcomes. The suggested structure of an IBD Unit includes a multi-disciplinary approach, effective referral processes, improved access using helplines, and departmental guidelines/pathways with identification of measurable quality indicators. Coordinated care models which incorporate a multi-disciplinary approach, structured clinical pathways or processes for the diagnosis, monitoring and treatment of IBD, fast-track recovery from IBD surgery, designated IBD clinics, virtual clinics and telemanagement are currently considered the main standards for process, although supporting data are limited. Several consensus statements on outcomes and quality indicators have been reported, focusing on outcomes in symptoms, function and quality of life restoration, survival and disease control, in addition to effective healthcare utilization. Conclusions: The results of this systematic review can provide the basis for general recommendations for standards of quality of care in IBD.